(untitled) (Amsterdam, 2006)
This book is the first to explore comprehensively one of the most fundamental trends which emerged in the last decade: to treat processors not as rigid, fixed entities, which designers include "as is" in their products; but rather, to build sound methodologies to tailor-fit processors to the specific needs of such products. This book addresses the goal of maintaining a very large family of processors, with a wide range of features, at a cost comparable to that of maintaining a single processor.
Keywords: Embedded computer systems,Embedded computer systems,Hệ thống máy tính nhúng; Design,Thiết kế